Solution on Wheels: A Strategic Plan for Launching an On-the-Go Mobile Laundry Service Focusing on Consumer Convenience and Efficiency - Buenaventura, JM; Francisco, Airisan; Manalili, Noemi; Peralta, Robin; Vega, Noemi (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines consumer behavior, preferences, and the feasibility of the “On the Go Mobile Laundry Service” in San Isidro, Nueva Ecija, focusing on convenience, pricing, service quality, and technological integration as determinants of adoption. Anchored in consumer behavior and technology adoption perspectives, the research employed a quantitative design using convenience sampling to collect data from busy professionals. Data were gathered through a structured survey questionnaire administered via digital platforms and analyzed using descriptive and inferential statistical techniques, including measures of central tendency. The findings indicate that respondents maintain structured laundry habits while experiencing significant time constraints, leading to a strong preference for convenience-based services. Although many still prefer home-based laundry, there is openness to mobile and pickup-and-delivery solutions. Results further show that time savings, convenience, and affordability are key motivators, while pricing concerns, trust issues, and service quality uncertainties remain major barriers. Respondents demonstrate willingness to pay for services that reduce time and effort, provided pricing is competitive and value-driven. Additionally, trust, customer reviews, and service reliability significantly influence adoption, while environmental awareness highlights a preference for eco-friendly and resource-efficient practices. The study concludes that mobile laundry services offer improved efficiency, reduced workload, and enhanced user experience, particularly when supported by user-friendly digital systems and sustainable practices. It recommends adopting customer-centered strategies, integrating digital tools, optimizing operations, and ensuring competitive pricing to enhance adoption and long-term viability. The study aligns with SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation and Infrastructure), SDG 11 (Sustainable Cities and Communities), and SDG 12 (Responsible Consumption and Production). It contributes to socio-economic, technological, and environmental sustainability by promoting efficient service delivery, supporting local entrepreneurship, and encouraging resource-efficient practices in urban communities.